2018
DOI: 10.1101/328732
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Patterns and perceptions of cannabis use with physical activity

Abstract: 26Abstract 27 Background and Aims: Past research has shown that cannabis use is common among adults in the U.S. In 28 addition, physical activity (PA), such as exercise, is often a component of many American's daily 29 routines. Anecdotal information suggests that a subset of individuals use cannabis in conjunction with 30 PA, but the evidence base is lacking. The purpose of this study was to assess the frequency, methods of 31 ingestion, strain types, and timing (before, during or after) of cannabis use in co… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…Since there is a high prevalence of substance use disorder in adults with BPD (Kienast et al, 2014) and substance use is linked to less PE (Abrantes and Blevins, 2019;Lisano et al, 2018;Martens et al, 2006;Werneck et al, 2019), three questionnaires were administered to assess substance use in our sample. The Cigarette Dependence Scale (CDS) evaluate cigarette addiction with 5 items answered on a 5-point Likert scale from 1 to 5.…”
Section: Baseline Measuresmentioning
confidence: 99%
“…Since there is a high prevalence of substance use disorder in adults with BPD (Kienast et al, 2014) and substance use is linked to less PE (Abrantes and Blevins, 2019;Lisano et al, 2018;Martens et al, 2006;Werneck et al, 2019), three questionnaires were administered to assess substance use in our sample. The Cigarette Dependence Scale (CDS) evaluate cigarette addiction with 5 items answered on a 5-point Likert scale from 1 to 5.…”
Section: Baseline Measuresmentioning
confidence: 99%
“…Acute cannabis consumption may reduce exercise pain and thus increase endurance (Huestis et al 2011 ), but chronic use does not. In survey research, most people using cannabis with exercise reported reduced pain and/or increased their enjoyment of the exercise activity (Lisano et al 2019a ; YorkWilliams et al 2019 ; Zeiger et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The remaining two studies relied entirely on self-reported cannabis use. Lisano et al ( 2019a , 2020 ) specified that participants be physically active; Maksud and Baron used labourers for their sample, who are generally active in their job; Wade, Gilbart, et al did not select participants based on fitness related factors. Three studies used a treadmill for VO2 measurement, while Maksud and Baron used a bicycle ergometer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since there is a high prevalence of substance use disorder in adults with BPD ( Kienast et al, 2014 ) and substance use is linked to less PE ( Abrantes & Blevins, 2019 ; Lisano et al, 2018 ; Martens et al, 2006 ; Werneck et al, 2019 ), three questionnaires were administered to assess substance use in our sample. The Cigarette Dependence Scale (CDS) evaluates cigarette addiction with 5 items answered on a 5-point Likert scale from 1 to 5.…”
Section: Methodsmentioning
confidence: 99%